2014
DOI: 10.3329/seajph.v3i1.17713
|View full text |Cite
|
Sign up to set email alerts
|

Fast food preferences and food habits among students of private universities in Bangladesh

Abstract: Consumption of takeaway and fast food by young adolescents is no longer confined to the developed countries; it has spread to the developing countries as well. The culture of fast food consumption has replaced the traditional meal among university students and is a great public health concern. Excessive consumption of fast food is responsible for obesity epidemics and the cause of a dramatic increase of obesity-related diseases (e.g. diabetes, heart diseases etc). A cross-sectional study was carried out from M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
43
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 13 publications
5
43
2
Order By: Relevance
“…University or college students, in particular, tend to have a high frequency of eating out and were likely to choose fast food when they eat out (Bipasha and Goon, 2014). Studies have indicated that university students tend to eat fast food at least once weekly (Driskell et al, 2006) frequently is often related to high consumption of fatty fast food and sugary soft drinks (Bipasha and Goon, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…University or college students, in particular, tend to have a high frequency of eating out and were likely to choose fast food when they eat out (Bipasha and Goon, 2014). Studies have indicated that university students tend to eat fast food at least once weekly (Driskell et al, 2006) frequently is often related to high consumption of fatty fast food and sugary soft drinks (Bipasha and Goon, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Hypercholesterolaemia became the most frequently encountered medical problem worldwide. Among its causes are the bad dietary habits and increased dependence on fast food [9]. Hypercholesterolaemia was reported to be linked to liver disease [42], cardiovascular diseases [28] and brain stroke [26].…”
Section: Introductionmentioning
confidence: 99%
“…7 In this issue, a paper examined the fast food consumption among graduate students in Bangladesh. 8 The findings are alarming as young adolescents are becoming addicted to fast food. It has been identified that fast food consumers usually young adults and educated than nonfast food consumers.…”
mentioning
confidence: 99%